Exploring the lived experiences of people on Community Correction Orders in Victoria, Australia: Is the opportunity for rehabilitation being realised? - Green, Rachael (The Australian and New Zealand journal of criminology, 2020)
The Community Correction Order, introduced in Victoria, Australia in 2012, provides a sentencing option that enables eligible offenders to serve their sanction in the community, with access to treatment or other rehabilitative activities. This paper contributes to a scant body of research investigating the specific needs of this group, their barriers to inclusion and the extent to which they experience the rehabilitative aspects of Community Correction Orders. It draws on survey data collected from 200 adults (137 men and 63 women) on Community Correction Orders in outer west metropolitan Melbourne and qualitative analysis of in-depth interviews conducted with a sub-set of 20 participants. Long-term unemployment, severe economic hardship, physical and mental health issues, social isolation and troubled personal relationships were common. While participants experienced the punitive aspects of Community Correction Orders, there was limited evidence that they were supported to address key issues that may be predictive of future offending. Support to re/engage in education, training and employment was a key area of unmet need and engagement in other therapeutic programs was low. Opportunities to enhance the rehabilitative potential of Community Correction Orders are discussed, with the paper highlighting that there is a need for rigorous evaluation of community work program activities.